Unhealthy lifestyle profile as a risk factor for poor quality of life and mental health in chronic kidney disease patients: a comparative case–control study - Beyrami, Maryam; Amiri, Sohrab (Frontiers in Medicine, 2025)
BackgroundThis study examined the mental health status and lifestyle of chronic kidney disease patients in comparison to a health control group. It also evaluated lifestyle factors as potential risk factors for kidney disease.MethodsThe case–control comparative study included chronic kidney disease (CKD) patients aged ≥18 years and a healthy control group. The primary outcomes were lifestyle profile, health-related quality of life, psychiatric morbidity, and somatic symptoms experiences. Associations between sociodemographic characteristics, health behaviors, and the risk of CKD were investigated using logistic regression, with odds ratios (ORs) and 95% confidence intervals (CIs) calculated. Independent t-tests were used to compare kidney patients with the healthy control group.ResultsThe CKD group scored lower in most aspects of lifestyle and health-related quality of life than the healthy control group. Additionally, CKD patients exhibited poorer mental health status than the healthy control group. Factors associated with chronic kidney disease risk include female gender, history of disease, and being retired. A health-promoting lifestyle among chronic kidney disease patients had a direct relationship with high health-related quality of life. Furthermore, a health-promoting lifestyle was negatively associated with mental health disorders and somatic symptoms experiences.ConclusionCompared to the healthy control group, CKD patients in this study reported more pain, physical complaints, and depression. A healthy lifestyle can be effective in the prevention and treatment of many physical and mental health problems. Compared to other treatments used for mental disorders, such as drug therapy or psychological therapy, lifestyle interventions can have long-lasting effects and tend to be more cost-effective for individuals.